Impact of Global Threats on Economic Security (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
The article examines the key threats arising from the processes of globalization. Validity and reliability of the results of the study is provided by the theoretical study of accumulated knowledge in science, an in-depth study of the scientific literature. The authors conclude that, despite the measures taken in modern conditions there are many global challenges and threats, which can have the most negative impact on national economic security in the short term. In this connection, the development of the economy is directly connected with the security of the country and should act as the most important factor providing it.
Keywords: Globalization; International Economic Processes; Economic Security; Economic Threats; Ensuring Economic Security